Foresight Studies in the Context of Innovation Policy of Ukraine in 2000s - Yegorov, I. (Наука та наукознавство, 2015)
Issues of science and technology forecasting in Ukraine are discussed in the broader context of innovation policy. A review of main tendencies in economic, R&D and innovation performance in the independent Ukraine is given. Contradictions of the State Innovation Policy in Ukraine are highlighted. Detailed review of the procedures involved in the two recent foresight programs in Ukraine (implemented in 2004 and in 2008–2011) is made. Main results of the recent foresight programs are summed up and the most important problems in foresight studies in Ukraine are outlined. It is emphasized that foresight activities in Ukraine were being implemented in conditions of very weak and incoherent innovation policy; responsibilities of the key actors were not well defined; they were used as a predominantly policy-informing tool; innovation policy building was based on normative considerations rather than on the analysis of future developments in technological and S&T areas.